Approach to prevention of musculoskeletal symptoms in dental students: an interventional study - Koni, Adela; Kufersin, Maria; Ronchese, Federico; Travan, Mauro; Cadenaro, Milena; Larese Filon, Francesca (La Medicina del Lavoro, 2018)
Background: Work-related musculoskeletal (MS) disorders are very common among dentists due to abnormal positions maintained during their work. There is the need to teach undergraduate students ergonomic procedures to prevent MS pain and disorders. Methods: All the students of the School of Dentistry at the University of Trieste were enrolled for the study (No. 55). A self-administered questionnaire was used to collect anthropometric information, previous or current diseases, MS pain and disorders and work tasks performed. All students attended a training course. Three months after the training they completed a follow-up questionnaire. Results: All students reported MS pain: higher at cervical level (91%), lower at lumbosacral level (64.2%), shoulders (43.6%), and wrist/hand level (41.8%). Forty-nine percent of students reported an improvement in pain symptoms (p<0.05) 3 months after the training. Conclusions: The prevalence of pain symptoms was high but the training course helped reduce symptoms. Theory and practice of ergonomics should be incorporated into dental undergraduate curricula.